THE EFFECT OF ECOLOGICAL FACTORS ON GROWTH OF Sterculia foetida L. IN BUON DON AND EA SUP DISTRICTS, DAK LAK PROVINCE - Trong Nhan Pham; Hong En Le; Khai Tan Pham (Tạp chí Khoa học Đại học Đà Lạt)
Accurate and reliable assessment of site suitability for the growth of selected plant species is critical for afforestation projects and programs to improve rural livelihoods. This research examines the relationship between growth of Sterculia foetida L. and six ecological factors in Buon Don and Ea Sup districts, Dak Lak Province. The purpose of the research is to predict the growth in average height and trunk diameter of the trees using ecological factors that are easy to measure and observe. These include topography (slope) and soil characteristics (clay ratio, depth of soil layer, surface and subsurface rock concentrations, and agglomeration ratio). The ecological factors were evaluated by multivariable regression analysis of growth data from 31 experimental plots, 16 in Buon Don district and 15 in Ea Sup district. The results show that four of the six factors affect average growth in tree height and that five factors affect average trunk diameter growth. The findings are of practical value for households and agricultural extension officers to consider before planting Sterculia foetida L. in the two areas.